OUTCOME OF HERNIATED LUMBAR DISC SURGERY BY FENESTRATION METHOD - Abdul Raqqaque Mari, Muhammad Ali Jamali, Muzmil Dilber, Shams Raza Brohi, Hamid Akber, Fahmida Arbab, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
.